Comparative Study of Different Treatment Processes for Durability Amelioration of Bamboo - Tripathi, Sadhna; Nautiyal, S. N. (Indian Forester, 2009)
Grave yard test on natural durability of five bamboo species i.e. Dendrocalamus strictus, Dendrocalamus giganteus, Bambusa balcooa, Bambusa nutans and Bambusa bambos shows none of the species is durable in ground contact. Treatment with copper chrome arsenic (CCA) at 4% concentration and four methods of treatment i.e. Boucherie, VAC-FRI, Wick and Diffusion were chosen for the study. Treated D. strictus performed excellently while B.nutans was completely damaged in grave yard test. Bamboos treated with CCA on the basis of their field performance can be arranged in the decreasing order of their performance as D. strictus b > D. Giganteus > B. balcooa > B. bambos > B. nutans. None of the treatment imparted considerable protection to Bambusa bambos and B. nutans. Boucherie performed best among all treatments applied and treatment methods can be graded as Boucherie > Diffusion > VAC-FRI > Wick process = Control on the basis of field performance. Moisture content, treatment time and retention of preservative had influenced performance of treated bamboo in field i.e. deterioration.